Bisphenol A‐induced mechanistic impairment of decidualization - Nelson, William; Adu‐Gyamfi, Enoch Appiah; Czika, Armin; Wang, Ying‐Xiong; Ding, Yu‐Bin (Molecular reproduction and development, 2020)
Decidualization is a crucial precedent to embryo implantation, as its impairment is a major contributor to female infertility and pregnancy complications. Unraveling the molecular mechanisms involved in the impairment of decidualization has been a subject of interest in the field of reproductive medicine. Evidence from several experimental settings show that exposure to bisphenol A (BPA), an endocrine‐disrupting chemical, affects the expression of several molecules that are involved in decidualization. Both low and high doses of BPA impair decidualization through the dysregulation of estrogen (ER) and progesterone (PR) receptors. Exposure to low doses of BPA leads to decreased levels and activities of several antioxidant enzymes, increased activity of endothelial nitric oxide synthase (eNOS), and increased production of nitric oxide (NO) via the upregulation of ER and PR. Consequently, oxidative stress is induced and decidualization becomes impaired. On the other hand, exposure to high doses of BPA downregulates ER and PR and impairs decidualization through two distinct pathways. One is through the upregulation of early growth response‐1 (EGR1) via increased phosphorylation of extracellular signal‐regulated protein kinases 1 and 2; and the other is through a reduced serum glucocorticoid‐induced kinase‐1 (SGK1)‐mediated downregulation of epithelial sodium channel‐α and the induction of oxidative stress. Thus, regardless of the dose, BPA can impair decidualization to trigger infertility and pregnancy complications. This warrants the need to adopt lifestyles that will decrease the tendency of getting exposed to BPA. Exposure to both low and high doses of bisphenol A during pregnancy affects decidualization through interfering with estrogen and progesterone receptors. Both doses can induce oxidative stress to impair decidualization. High doses impair through the upregulation of early growth response‐1 and downregulation of epithelial sodium channel‐α.